ANALISIS TREN TINGKAT PENGANGGURAN TERBUKA (TPT) DAN PERAN SEKTOR PARIWISATA DI PROVINSI BALI (2015–2025) - Dina Jamsari; Fika Aulia Rahma (PT. Hasba Edukasi Mandiri, 2026)
Bali Province has the lowest open unemployment rate (OUR) in Indonesia. This study aims to analyze trends in the OUR in Bali Province during the 2015–2025 period and identify the role of the tourism sector in labor absorption. The method used is quantitative descriptive with trend analysis based on secondary data from the Bali Provincial Statistics Agency. The analysis focuses on the UER, Labor Force Participation Rate (LFPR), and GRDP of the Accommodation and Food Services sector as a proxy for tourism. The results indicate that Bali’s unemployment rate trend was highly volatile, remaining stable at a low level below 2% during 2015–2019, surging sharply to 5.63% due to the COVID-19 pandemic in 2020, and demonstrating resilience in recovery, projected to return to 1.49% by 2025. Visual analysis confirms an inverse relationship between tourism GRDP growth and the unemployment rate. When the tourism sector contracted by -27.50% in 2020, the unemployment rate rose sharply. Conversely, the post-pandemic recovery of the tourism sector became the primary driver in reducing the TPT rate again.